Using Capacitance Sensors for the Continuous Measurement of the Water Content in the Litter Layer of Forest Soil - Mioko Ataka; Yuji Kominami; Takafumi Miyama; Kenichi Yoshimura; Mayuko Jomura; Makoto Tani (Applied and Environmental Soil Science)
Little is known about the wetting and drying processes of the litter layer (L layer), likely because of technical difficulties inherent in nondestructive water content (WC) monitoring. We developed a method for continuously measuring the WC of leaf litter (the “LWC method”) in situ using capacitance sensors. To test variants of this approach, five (for the LWC_5) or ten (for the LWC_10 method) Quercus serrata leaves were attached around capacitance sensors. The output voltage used for each LWC method was linearly correlated with the gravimetric WC (LWC_5: R2=0.940; LWC_10: R2=0.942), producing different slopes for each calibration line. For in situ continuous measurements of WC in the L layer, two sensors were used, one placed on top of the L layer and the other at the boundary between the L and mineral layers. The average continuous WC of the L layer was then calculated from the output voltage of the two sensors and the calibration function, and this value was linearly correlated with the gravimetric WC (R2=0.697). However, because the L layer characteristics (e.g., thickness, water-holding capacity, and species composition) may differ among study sites, appropriate approaches for measuring this layer’s moisture properties may be needed.